Job Satisfaction and Training Investments - Obst, Cosima (Institutional Repository of the University of Potsdam, 2022)
Job satisfaction has been found to impact behavioral choices at the workplace. Since levels of satisfaction are not guaranteed to remain high, understanding the consequences of job dissatisfaction is essential. Hence, I analyze the relationship between a worker’s job satisfaction and her training investments. Based on my theoretical model, I expect a U-shaped relationship if dissatisfied workers attempt to improve the situation or plan to quit. In contrast, there is an overall positive relationship if dissatisfied workers neglect their duties. Using logit regressions with the Household, Income and Labour Dynamics in Australia (HILDA) survey I find tentative evidence that there is on average an overall positive relationship with a 1 standard deviation increase in job satisfaction being associated with a 1.5% increased likelihood of participating in training. A closer inspection of the reasons for training as well as quit intentions reveals some hints of a U-shaped relationship. My results highlight the importance of considering the source of dissatisfaction as there are heterogeneous effects along different job satisfaction facets.
Keywords: Health and wellbeing; Labour market; Learning, education and training